Socialization and Implementation Product Drinks Ginger Powder in Tugu Village, Mantup Subdistrict, Lamongan District - Luthfiah, Siti Zubaidah; Pamukir, Diah Ayu (Kontribusia : Research Dissemination for Community Development, 2024)
Tugu Village is one of the villages located in Mantup District, Lamongan Regency. Village monument consists from 2 Hamlet, that is Hamlet monument And Hamlet Hair. Area conditions Village monument is plain low with land productive Which used for rice fields. The economy in Tugu Village is very diverse and this can be seen in terms of the residents' livelihoods. Tugu Village Thematic KKN students will invite socialization to public For make product drink powder ginger. Product powdered drink ginger Can beneficial as warmer body And treat flu. Product This It is not only used as a body warmer during the rainy season, because ginger has many other benefits such as pain relief and increasing the body's immunity. By processing ginger into powdered ginger, the ginger will last a long time without the need for preservatives and is ready to be brewed whenever needed. Using the principle of crystallization which is based on utilizing the properties of granulated sugar (sucrose). return form crystal after melted. Method Implementation Which There are three stages, namely the Preparation Stage, the Counseling Stage and the Planning Stage. Activity This done so that public Village monument Can make knowledge about making powdered ginger drink as a business opportunity. The hope is also to improve the economy and welfare of the residents of Tugu Village.